Meriones shawi - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Meriones shawi (Duvernoy, 1842). Mem. Soc. Sci. Nancy, 3:22. TYPE LOCALITY: Algeria, Oran, 35° 42' N „ 0° 38' W. DISTRIBUTION: Morocco to N. Algeria, Tunisia, and Egypt. COMMENT: Considered a distinct species by Lay and Nadler, 1969, Cytogenetics, 8: 35-50, Harrison, 1972, The Mammals of Arabia, 3:593, and Petter, 1975, Part 6.3:4. Includes granáis and isis; see Petter, 1975, Part 6.3:4, and Corbet, 1978:127. Lay, 1981, in Utt., considered granáis a distinct species. Setzer, 1961, J. Egypt Public Health. Assoc., 36:81-90, and Ranck, 1968, Bull. U.S. Nat. Mus., 275:1 -264, referred to specimens of shawi as libycus. DML considers shawi a valid species, readily distinguishable from libycus. Formerly included tristrami; see Corbet, 1978:126. ISIS NUMBER: 5301410008092009001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 3), pp. 392-476 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 425, DOI: 10.5281/zenodo.7353031